Successful resolution of the ophthalmic manifestations of a falcotentorial meningioma through Cerebrospinal fluid diversion. (January 2020) - Pham, Chengde; McAlpine, Heidi; Tee, Jin Wee
Highlights: We present a unique case of a large falcotentorial meningioma manifesting only with subtle abducens nerve paresis. Management of these uncommon lesions remains challenging despite modern day surgery. Complete surgical resection is the definitive therapeutic option but is associated with significant potential morbidity. Cerebrospinal fluid diversion without resection may be advocated in certain cases, particularly if relatively asymptomatic. Abstract: We report the case of a falcotentorial meningioma presenting only with binocular, horizontal diplopia in an otherwise healthy sixty-two-year old male. Review of the established literature highlights a lack of consensus regarding management of this extremely rare pineal region tumor. Complete surgical resection ultimately remains the ideal therapeutic option but surgical excision continues to bear serious risk of neurologic and ophthalmic morbidity, including hemianopia and cortical visual impairment. We advocate that a multidisciplinary approach focusing on patient values is critical in treatment of these uncommon lesions. Cerebrospinal fluid diversion in this patient achieved successful resolution of symptoms secondary to intracranial hypertension whilst facilitating close surveillance.